Psychological Resilience: An Affect-Regulation Framework - Troy, Allison S; Willroth, Emily C; Shallcross, Amanda J; Giuliani, Nicole R; Gross, James J; Mauss, Iris B (Annual review of psychology, 2023)
Exposure to adversity (e.g., poverty, bereavement) is a robust predictor of disruptions in psychological functioning. However, people vary greatly in their responses to adversity; some experience severe long-term disruptions, others experience minimal disruptions or even improvements. We refer to the latter outcomes-faring better than expected given adversity-as psychological resilience. Understanding what processes explain resilience has critical theoretical and practical implications. Yet, psychology's understanding of resilience is incomplete, for two reasons: ( ) We lack conceptual clarity, and ( ) two major approaches to resilience-the stress and coping approach and the emotion and emotion-regulation approach-have limitations and are relatively isolated from one another. To address these two obstacles,we first discuss conceptual questions about resilience. Next, we offer an integrative affect-regulation framework that capitalizes on complementary strengths of both approaches. This framework advances our understanding of resilience by integrating existing findings, highlighting gaps in knowledge, and guiding future research.